Effect of transcutaneous electrical acupuncture point stimulation on expression of p-JNK in the dorsal root ganglion in a rat model of myofascial pain syndrome. Issue 5 (October 2019) - Yu, Xiangdi; Zhang, Fangxiang; Zhang, Jingchao
Background: Acupuncture has been used to treat myofascial pain syndrome (MPS) for 2000 years in China, but its mechanisms are still not entirely clear. In the present study, we explored the effects of transcutaneous electrical acupuncture point stimulation (TEAS) at an Ashi acupuncture point on expression of phosphorylated c-Jun N-terminal kinase (p-JNK) in the dorsal root ganglion (DRG) using a rat model of MPS. Methods: 32 rats were divided into four groups: normal, MPS, MPS+TEAS and MPS+sham- TEAS. MPS was produced by a blunt strike to the left vastus medialis combined with eccentric exercise for 8 weeks. Rats in the MPS+TEAS group received TEAS (6–9 mA, 2 Hz, 30 min) treatment at the Ashi acupuncture point for 2 weeks; rats in the MPS+sham -TEAS group had the same electrodes applied but received no stimulation. Paw withdrawal thermal latency (PWTL) was studied at baseline and on days 3, 7, 11 and 15 after treatment. Haematoxylin and eosin staining was used to examine for morphological changes in the left vastus medialis muscles; expression of p-JNK in the L3–L5 DRG was determined by immunofluorescence staining and western blotting after treatment. Results: Compared with the normal group, PWTL decreased significantly (P<0.01) and the expression of p-JNK in the DRG increased in the MPS and MPS-sham-TEAS groups (P<0.01); compared with the MPS group, PWTL was increased significantly (P<0.01) and expression of p-JNK in the DRG was decreased in the MPS+TEAS group. However, when compared with the normal group, PWTL did not recover to baseline and expression of p-JNK was still higher. Conclusion: TEAS treatment may produce an analgesic effect, probably by inhibiting the expression of p-JNK in the DRG of rats with MPS.